Herbicide-resistant weeds: From research and knowledge to future needs - Busi, R.; Vila-Aiub, M.; Beckie, H.; Gaines, T.; Goggin, D.; Kaundun, S.; Lacoste, Myrtille; Neve, P.; Nissen, S.; Norsworthy, J.; Renton, M.; Shaner, D.; et al. (Wiley-Blackwell Publishing, Inc., 2013)
Synthetic herbicides have been used globally to control weeds in major field crops. This has imposed a strong selection for any trait that enables plant populations to survive and reproduce in the presence of the herbicide. Herbicide resistance in weeds must be minimized because it is a major limiting factor to food security in global agriculture. This represents a huge challenge that will require great research efforts to develop control strategies as alternatives to the dominant and almost exclusive practice of weed control by herbicides. Weed scientists, plant ecologists and evolutionary biologists should join forces and work towards an improved and more integrated understanding of resistance across all scales. This approach will likely facilitate the design of innovative solutions to the global herbicide resistance challenge. © 2013 The Authors. Evolutionary Applications published by John Wiley & Sons Ltd.